2018
DOI: 10.15252/embj.201797138
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic transcriptional interference regulates the human immune ligand MICA

Abstract: Many human genes have tandem promoters driving overlapping transcription, but the value of this distributed promoter configuration is generally unclear. Here we show that , a gene encoding a ligand for the activating immune receptor NKG2D, contains a conserved upstream promoter that expresses a noncoding transcript. Transcription from the upstream promoter represses the downstream standard promoter activity in through transcriptional interference. The effect of transcriptional interference depends on the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…Throughout development, alternative promoters and alternative TSSs are activated leading to increased transcript diversity [4]. Several single-locus studies have demonstrated that TSS switching events occur via mechanisms similar to that described in yeast [30,79]. In addition, diseases such as cancers and neurodevelopmental disorders such as autism and epilepsy are associated with pervasive misregulation of alternative promoters [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout development, alternative promoters and alternative TSSs are activated leading to increased transcript diversity [4]. Several single-locus studies have demonstrated that TSS switching events occur via mechanisms similar to that described in yeast [30,79]. In addition, diseases such as cancers and neurodevelopmental disorders such as autism and epilepsy are associated with pervasive misregulation of alternative promoters [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…A prime example may turn out to be plant light signaling that relies on alternative TSS choices [49], as we observed for the AT4G15260 gene. Furthermore, recent examples of gene regulation by the act of interfering lncRNA transcription in yeast and human emphasize a key role for FACT [7, 37, 38]. While such examples remain to be characterized in plants, we demonstrate that the underlying mechanism of repressive RNAPII transcription is operational.…”
Section: Discussionmentioning
confidence: 64%
“…Although not applied in pre-clinical studies, a number of early works also suggest that dCas9-based methods can help circumvent other major tumor immunoevasion mechanisms. For instance, impairment of Treg immunosuppressive function by dCas9-KRAB-mediated forkhead box P3 (FoxP3) transcriptional repression, 139 , 140 dCas9-SAM-mediated enhancement of neoplastic transformation markers, such as MICA, 141 , 142 and dCas9-KRAB-directed repression of immunosuppressive cytokine receptors 143 have demonstrated that dCas9-mediated epigenetic engineering has potential in multiple facets of cancer immunotherapy. Ultimately, dCas9-mediated epigenetic editing to improve tumor immunogenicity and/or boost the host’s anti-tumor immune response opens new therapeutic avenues, particularly in combination with ICI or ACT therapies ( Figure 2 ).…”
Section: Epigenetic Editing By Crispr-dcas9 Can Improve Anti-tumor Host Immunitymentioning
confidence: 99%